Stories of a killer virus : a framing analysis of the press coverage of Sars in Singapore and China - Neo, Jaclyn Ah Peng (2008)
By a detail content analysis, this study differentiated the framing approach by the press of THe Straits Times of Singapore and People's Daily of China.